The Effect of Business Development of Lobster Cultivation on Sales Volume in Lamanggau Village, Tomia District, Wakatobi Regency - robin, robin; basri, muhammad; abdullah, akhyar (Universitas Halu Oleo, 2017)
This study aims to describe the Effect of Lobster Farming Business Development on Sales Volume in Lamanggau Village, Tomia District, Wakatobi Regency. The research was conducted in January 2016 in Lamanggau Village, Tomia District, Wakatobi Regency. In this study, researchers used a quantitative approach to data analysis carried out with stages, including; Data reduction, data presentation and drawing conclusions. The results showed that Lobster Cultivation in Lamanggau Village, Tomia Subdistrict, Wakatobi Regency was very large because it had a large number of cultivation places (karamba) so that the level of lobster production in this village experienced an increase in each harvest and each sale. The suggestions from this research are for the government and related parties in economic empowerment and to strengthen the Lobster Cultivation Business and are expected to the relevant agencies to be able to help market the Lobster Business products so that Lobster Business in Lamanggau Village can be widely known by the community and obtain capital and financial assistance to develop their business, it is expected that Lobster entrepreneurs will improve their skills and product quality so that in carrying out production and marketing activities more efficiently